Internment during the First World War
1 online resource (xv, 298 pages).
Keywords: "Although civilian internment has become associated with the Second World War in popular memory, it has a longer history. The turning point in this history occurred during the First World War when, in the interests of 'security' in a situation of total war, the internment of 'enemy aliens' became part of state policy for the belligerent states, resulting in the incarceration, displacement and, in more extreme cases, the death by neglect or deliberate killing, of hundreds of thousands of people throughout the world. This pioneering book on internment during the First World War brings together international experts to investigate the importance of the conflict for the history of civilian incarceration"--